2021
DOI: 10.1186/s12889-021-11341-3
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between dietary patterns and overweight and obesity among adult in Jiangsu Province of China: a structural equation model

Abstract: Aims This study aimed to analyze the relationship between diet and overweight and obesity in Jiangsu Province by using structural equation modeling (SEM), and to determine dietary differences between genders in the model. Methods Data from 1739 individuals (53.8% female, n = 935) were analyzed. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were used to classify dietary patterns. SEM and multivariate logistic regression we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Moreover, social support also enhances the life satisfaction of children which results in better psychological wellbeing. Additionally, social support contributes to a higher level of mental wellbeing regardless of stress and pressure (Wang et al, 2021 ). Social support allows the children to communicate and share problems with others in the society which leads to the better mental wellbeing of children.…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%
“…Moreover, social support also enhances the life satisfaction of children which results in better psychological wellbeing. Additionally, social support contributes to a higher level of mental wellbeing regardless of stress and pressure (Wang et al, 2021 ). Social support allows the children to communicate and share problems with others in the society which leads to the better mental wellbeing of children.…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%
“…In their 2019 longitudinal study, Neri-Sanchez et al also underlined the positive association between adherence to a "Risky" dietary pattern, including high fat and high sugar content, with the presence of central obesity in Mexican adults [25]. A different pattern consisting of poultry, vegetables, red meat, and red meat products, among others, was also associated with obesity in male, Chinese adults, in a 2021 study of 1739 adults by Wang et al [26].…”
Section: Discussionmentioning
confidence: 96%
“…Using SEM, we evaluated the full mediate effects via DAL proxy of three mentioned dietary patterns on NAFLD. Although an indirect pathway between dietary patterns and potential adverse health effects such as obesity has been mentioned in the literature ( 57 ), empirical studies are limited on this subject. Ghaemi et al ( 58 ), in a cross-sectional study conducted among 1,500 individuals referred to a nutrition clinic, reported the putative role of waist circumference as a mediator in the relationship between unhealthy and healthy dietary patterns and NAFLD.…”
Section: Discussionmentioning
confidence: 99%